Answer:
Option B is correct.
The expression which is equivalent to
is; ![(n+22)(n+4)](https://tex.z-dn.net/?f=%28n%2B22%29%28n%2B4%29)
Explanation:
Given the equation:
for all values of n.
The quadratic equation in this form; ![ax^2+bx+c =0](https://tex.z-dn.net/?f=ax%5E2%2Bbx%2Bc%20%3D0)
First find two numbers that multiply to give ac and add to give b.
From the given equation;
a =1 , b = 26 and c =88
then,
the two number that multiply to give ac =88 is, 22 or 4
and they add up to give b=26 (i.e 22+4)
Now, rewrite the middle term i.e 26n with 22n and 4n , we have
![n^2+22n+4n+88=0](https://tex.z-dn.net/?f=n%5E2%2B22n%2B4n%2B88%3D0)
Now, factor the first two terms and last two terms,
![n(n+22)+4(n+22)](https://tex.z-dn.net/?f=n%28n%2B22%29%2B4%28n%2B22%29)
we see that
is common to both terms so, we have;
![(n+22)(n+4)](https://tex.z-dn.net/?f=%28n%2B22%29%28n%2B4%29)
Therefore, the expression
is equivalent to
Check:
(n+4)(n+22) =
=
[ True]
Answer:Angles 1 and 3 are vertical angles
Step-by-step explanation:
Recall the secant-tangent theorem, and you have
EA^2 = EC*CD
12^2 = 8*(x+10)
and now ED = EC+CD = 8+x+10
I suspect a typo somewhere in the murk above
BRO I DONT KNOW ANSWER EAST OR WEAST MY ANSWER IS BEST
Answer:
3/8 cups
Step-by-step explanation:
divide 3/4 by two